West Coast Exile: A Scottish-Canadian Bard in the United States at the Turn of the Twentieth Century - Little, Jack (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2011)
Most of the crofters forced off the Isle of Lewis by the potato famine of the 1840s became colonists on the rugged northern Appalachian frontier of Canada East (the province of Quebec) where they reconstituted many elements of their close-knit Gaelic-speaking society. While their new settlements were largely homogenous, the fact that families depended upon the wages of young men and women sojourning in the United States resulted in cultural assimilation, permanent out-migration, and population decline, so that there was little left of this once-vibrant Highland community by the early twentieth century. While the Quebec Scots became widely dispersed across the continent during this second exodus, identifiable communities formed in American cities such as Springfield, Massachusetts, and Seattle, Washington, where they continued to depend upon each other for support. This essay will examine that support network, and the emotional cost of emigration, largely through the writing of a Canadian-born bard who spent much of his adult life in the United States.